2005
DOI: 10.1159/000083234
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Metoclopramide and Domperidone on HERG Channels

Abstract: Torsades de pointes (TdP) is a potentially fatal form of ventricular arrhythmia that occurs under conditions where cardiac repolarization is delayed (as indicated by prolonged QT intervals from electrocardiographic recordings). A likely mechanism for QT prolongation and TdP is blockade of the rapid component of the cardiac delayed rectifier K+ current (IKr), which is encoded by HERG (human ether-a-go-go-related gene). The gastroprokinetic agent cisapride is a potent blocker of HERG curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…PPB are either from published data (plain text) or measured in our laboratories (bold italics). [22]; c: [23]; d: [24,25]; e: [26]; f: [27]; g: [28]; h: [19]; i: [29]; j: [30]; k: [31]; l: [32]; m: [33]; n: [34]; o: [35]; p: [36]; q: [37]; r: [38]; s: [39]; t: [40]; u: [41]; v: [42]; w: [43]; x: [44]; y: [45]; z: [46]; aa: [47]; bb: [48]; cc: [49]; dd: [50]; ee: [51]; ff: [52]; gg: [53]; hh: [54]; ii: [55]; jj: [56]; kk: [57]; ll: [58]; mm: [59]; nn: [60]; oo: [61]; pp: [62]; qq: [63]; rr: [64]; ss: [65]; tt: [66]; uu: [67]; vv: [68]; ww: …”
Section: Drugs With a Cardiovascular Target Without A Direct Role In mentioning
confidence: 99%
“…PPB are either from published data (plain text) or measured in our laboratories (bold italics). [22]; c: [23]; d: [24,25]; e: [26]; f: [27]; g: [28]; h: [19]; i: [29]; j: [30]; k: [31]; l: [32]; m: [33]; n: [34]; o: [35]; p: [36]; q: [37]; r: [38]; s: [39]; t: [40]; u: [41]; v: [42]; w: [43]; x: [44]; y: [45]; z: [46]; aa: [47]; bb: [48]; cc: [49]; dd: [50]; ee: [51]; ff: [52]; gg: [53]; hh: [54]; ii: [55]; jj: [56]; kk: [57]; ll: [58]; mm: [59]; nn: [60]; oo: [61]; pp: [62]; qq: [63]; rr: [64]; ss: [65]; tt: [66]; uu: [67]; vv: [68]; ww: …”
Section: Drugs With a Cardiovascular Target Without A Direct Role In mentioning
confidence: 99%
“…An inverted Zeiss LSM-510 laser-scanning confocal imaging system with an argon laser (excitation wavelength: 488 nm) was employed and EGFP-induced fluorescence (>505 nm) was detected using a photomultiplier tube. HERG currents were recorded as described recently (Claaßen and Zünkler, 2005). HERG current signals were filtered at 2 kHz with the help of a Bessel filter (902, Frequency Devices, Haverhill, Massachusetts, USA).…”
Section: Electrophysiological Recordingmentioning
confidence: 99%
“…18 Interestingly, one in vitro study showed that both metoclopramide and domperidone bind to and block hERG (human ether-à-go-gorelated gene) channels in a concentration-dependent manner. 19 Blockade of the hERG channel is a likely mechanism for QTc prolongation, and it has been shown that domperidone is a more potent blocker of hERG currents (by a factor of 100) than metoclopramide; however, this finding has not been confirmed in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro data have suggested a concentrationdependent prolongation of the QTc interval, which in turn suggests a potential dose-response relationship. 19 Conversely, domperidone is eliminated mostly hepatically, with less than 1% renal excretion of unchanged drug. 22 Therefore, this drug does not significantly accumulate in patients with renal impairment.…”
Section: Discussionmentioning
confidence: 99%